The Persistence of Warps in Spiral Galaxies with Massive Halos - Binney, J; Jiang, I; Dutta, S (1997)
We study the persistence of warps in galactic discs in the presence of massive halos. A disc is approximated by a set of massive rings, while a halo is represented by a conventional n-body simulation. We confirm the conclusion of Nelson and Tremaine (1995) that a halo responds strongly to an embedded precessing disc. This response invalidates the approximations made by in the derivation of classical `modified tilt' modes. We show that the response of the halo causes the line of nodes of a disc that starts from a modified tilt mode to wind up within a few dynamical times. We explain this finding in terms of the probable spectrum of true normal modes of a combined disc-halo system.